2004
DOI: 10.1097/00006676-200408000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Histologic and Immunohistochemical Comparison of Intraductal Tubular Carcinoma, Intraductal Papillary-Mucinous Carcinoma, and Ductal Adenocarcinoma of the Pancreas

Abstract: The PCNA-L.I of IPMC and ITC was lower and the cell atypia of them was more mild compared with those of ductal carcinoma, indicating that IPMC possess low-grade malignant potentials. However, we observed differences of growth patterns and mucous secretion between ITC and IPMC of the pancreas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 17 publications
3
44
0
Order By: Relevance
“…8,14,15,17,30,32,33 The neoplasm is composed of closely packed tubular glands and occasionally contains markedly complex cribriform glands and solid areas. 12,32,33 The tumor cells show eosinophilic cytoplasm and atypical nuclei. Immunohistochemical examination has revealed that ITC cells are focally positive for MUC1, but negative for MUC2 and MUC5AC.…”
Section: Discussionmentioning
confidence: 99%
“…8,14,15,17,30,32,33 The neoplasm is composed of closely packed tubular glands and occasionally contains markedly complex cribriform glands and solid areas. 12,32,33 The tumor cells show eosinophilic cytoplasm and atypical nuclei. Immunohistochemical examination has revealed that ITC cells are focally positive for MUC1, but negative for MUC2 and MUC5AC.…”
Section: Discussionmentioning
confidence: 99%
“…[84][85][86][87] High expression levels of MUC1 and MUC4 have been detected in pancreatic cancer tissues and tumor cell lines, whereas their expression was undetectable in normal pancreas samples. 9,84,85,[88][89][90][91][92] An increase of the cellular levels of these mucins also seems to correlate with the progression of pancreatic cancer. 84,89,91 In this matter, it has been observed that MUC1 expression in human pancreatic cancer S2-013 cells was accompanied in vitro by increasing the invasiveness and motility of cells.…”
Section: Mucin Signalingmentioning
confidence: 99%
“…However, many tumor nodules show no residual non-neoplastic ductal epithelium at the periphery (135). The nodules are composed of either back to back tubular glands or punctuated sheets of tumor cells ( Figure 7B) (54,134,138). Despite the entity's name, the predominant growth pattern is tubular in ITPNs with papilla formation seen only focally in rare cases (135,139).…”
Section: Pathologic Featuresmentioning
confidence: 99%
“…However, because (7,134) many of the individual tumor nodules lack a peripheral rim of nonneoplastic ductal epithelium, it is often very difficult to determine whether invasive carcinoma is present (24,138). Foci in which there are thin strands of cells extending away from the edges of the nodules are regarded to represent stromal invasion (Figure 8).…”
mentioning
confidence: 99%